Pelatihan Dendang Syair Melayu di SMA PGRI Pekanbaru - Arman, Idawati; Muslim, Muslim; Sofiani, Radika; Iliana, Endang (Community Education Engagement Journal, 2019)
This service activity aims to introduce and pursue the variety of Malay poetry singing to high school students. This is motivated by the lack of the existence of Malay poetry singers in young people in Pekanbaru. With the meaning of the word showing deterioration in quantity, even though this art still thrives in the midst of its supporting community. This reduction in the number of singer in Pekanbaru, can be seen in every event, which only often shows old poets. This is due to the lack of knowledge transfer of this art branch among the younger generation, especially in the world of education. Even the presence of Local Content subjects in schools is not qualified enough to anticipate this situation. This is made possible by the lack of skilled educators in schools, so students are less interested in learning it. Responding to this situation, training on poetry singing in class rooms in schools is deemed necessary to implement, namely by providing direct training to school students. The effective method used for this training is to use the demonstration method. With the training the singing of poetry, it is hoped that it will open a sense of wanting to learn more about the variety of rhythms of Malay poetry, especially for students at SMA PGRI Pekanbaru.